Striga-resistant cowpea - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Striga is a parasitic weed that causes devastation to several crops in Africa. Different species of striga attack different crops the species of striga which parasitizes maize and sorghum IS different from that which attacks cowpea. Seeds of striga...